Membrane-dependent uridylylation of the genome-linked protein VPg of poliovirus. - Takegami, T (1983)
A small nucleotidyl-protein has been synthesized in vitro in a membrane fraction of poliovirus-infected HeLa cells. Analyses of the nucleotides and polypeptide have shown that the nucleotidyl-protein is VPg-pUpU: the genome-linked protein of poliovirion RNA covalently bound to the first two 5'-terminal nucleotides of poliovirus RNA. Synthesis of VPg-pUpU in vitro was sensitive to nonionic detergent. We suggest that VPg-pUpU is part of the initiation complex in poliovirus RNA replication in a membranous environment.